HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMANDIRIAN LANSIA DALAM MELAKSANAKAN PERSONAL HYGIENE DI KABUPATEN GIANYAR: THE CORRELATION BETWEEN FAMILY SUPPORT WITH INDEPENDENCE OF THE ELDERLY IN IMPLEMENTING PERSONAL HYGIENE IN GIANYAR REGENCY - Kirawan, I Komang Yoki; Prihatiningsih, Diah (Stikes Wira Medika Bali, 2020)
Personal hygiene is the ability of a person to take care of himself starting from sleeping, bathing, dressing and so on until he goes to sleep again, or all activities of people who take care of themselves. To achieve this goal family support is needed as one of the interpersonal factors to achieve the independence of the elderly in implementing personal hygiene. This study aims to determine the relationship of family support with the independence of the elderly in carrying out personal hygiene This study used cross sectional. The sampling technique in this study used all sampling with 45 samples. The results of the Rank Spearman correlation test showed that the correlation coefficient (r) = 0.425 with a strong and positive correlation coefficient with a p value = 0.004 (p <a) which means there is a relationship between family support and elderly independence in implementing personal hygiene in Gianyar Based on the findings above can provide input and information for the community especially to further improve personal hygiene in the elderly to be better.